Using role-piaying game in medical students clinical skills mastering during study the theme: "Counseling HIV infected patients" - Stepanovichus, O. M.; Rozhkovska, N. M.; Golubenko, M. Y. (Journal of Education, Health and Sport, 2017)
Stepanovichus O. M., Rozhkovska N. M., Golubenko M. Y. Using role-piaying game in medical students clinical skills mastering during study the theme: "Counseling HIV infected patients". Journal of Education, Health and Sport. 2017;7(1):346-349. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.267979 http://ojs.ukw.edu.pl/index.php/johs/article/view/4224 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. UDK: 372.8:618.1/.2:061.3 USING ROLE-PlAYING GAME IN MEDICAL STUDENTS CLINICAL SKILLS MASTERING DURING STUDY THE THEME: "COUNSELING HIV INFECTED PATIENTS " O. M. Stepanovichus, N. M. Rozhkovska, M.Y. Golubenko Odessa National Medical University Odessa, Ukraine Abstract Providing better absorption and consolidate the clinical skills for medical students for counseling HIV-infected patients involves a learning process during the role-playing games, which will contribute to the promotion and improvement of mastering complex clinical material. Key words: medical university, medical education, role-playing game, HIV infection.